Improving the Methodology for Forming Computational Skills in Primary School Students - Usmonova Z. I. (International Journal on Integrated Education, 2022)
Relevance. The formation of mental counting skills occupies a special place in elementary school and is one of the main tasks of teaching mathematics at this stage. It is in the first years of training that the basic methods of oral calculations are laid, which activate the mental activity of students, develop memory, speech, and the ability to perceive what is said by ear in children, increase attention and speed of reaction.